2018
DOI: 10.20473/fmi.v54i4.10715
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Insomnia and Its Association with Social Media Usage among University Students in Selangor, Malaysia, 2018

Abstract: Insomnia is an arising common health problem in Malaysia. There are many factors contributed to insomnia in young adults but very few are known. Increasing usage of social media may be one of the contributing factors to insomnia along its association with the sociodemographic factors. The objective of this study was to measure the prevalence of insomnia and to study its association with usage of social media and sociodemographic factors among university students. A cross-sectional based questionnaire was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…This is close to the rate of 25% reported by the study conducted in Iraq (Piro et al, 2018). On the other hand, this is notably different to percentages reported in American and Asian cohorts at 12% and > 68%, respectively (Abdalqader et al, 2018;Gaultney, 2010;Sing & Wong, 2010). In contrast, other sleep disorders like OSA, affective disorders, and CRDs were much less frequently reported in the present study, with prevalence rates of 21.5%, 14.1%, and 9.1%, respectively.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This is close to the rate of 25% reported by the study conducted in Iraq (Piro et al, 2018). On the other hand, this is notably different to percentages reported in American and Asian cohorts at 12% and > 68%, respectively (Abdalqader et al, 2018;Gaultney, 2010;Sing & Wong, 2010). In contrast, other sleep disorders like OSA, affective disorders, and CRDs were much less frequently reported in the present study, with prevalence rates of 21.5%, 14.1%, and 9.1%, respectively.…”
Section: Discussionsupporting
confidence: 68%
“…In particular, insomnia, restless leg syndrome (RLS), circadian rhythm disorders (CRDs), affective disorders, narcolepsy, and obstructive sleep apnoea (OSA) are frequently reported in college students (Gaultney, 2010;Haile et al, 2017;Piro et al, 2018). Previous studies have found the prevalence of insomnia to be approximately 69% among college students (Abdalqader et al, 2018;Sing & Wong, 2010). Other disorders, like CRDs (19.6%), affective disorders (14.5%), nightmares (6.6%), sleepwalking (5.7%), and narcolepsy (1.3%), are less frequently identified (Piro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These factors could affect the function of the liver, resulting in interruptions of qi and blood, which can lead to a variety of problems, including mood swings and depression [ 19 ]. Additionally, poor sleep quality and insomnia in university students [ 113 ] could influence the liver’s blood storing ability, thus affecting its dispersion and dredging function, which will then cause qi-stagnation [ 19 ]. Dysregulation of the liver qi is the main cause of depression, and is associated with the neuroendocrine system [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…27 The duration and frequency of SM use also provoked insomnia. 28 Inversely, a Lebanese study showed that university students that reported higher depression and anxiety scores, as well as poor sleeping patterns, were more likely to have a smartphone addiction. 29 Results also demonstrated a relation between less sleep and Internet gaming disorder within a Lebanese sample.…”
mentioning
confidence: 99%